Quality of life of smokers and its correlation with smoke load (Fisioterapia e Pesquisa, 2017)
Smoking is considered a chronic disease and one of the leading causes of preventable death in the world. The quality of life is an important measure of health impact and its correlation with nicotine dependence levels and smoking is unclear. We evaluated the quality of life of smokers and its correlation with smoke load and the nicotine dependence level. Smokers of both sexes and with no diagnosis of clinical diseases were included in this study. We evaluated their quality of life and level of nicotine dependence through questionnaires. The sample consisted of 48 individuals, 27 women and 21 men. There was a negative correlation between vitality and the amount of years these individuals have smoked (p=0.009;r=-0.27), as well as the general health condition and pack/years (p=0.02; r=-0.23), and the current amount of cigarettes consumed per day (p=0.006;r=-0.29). We can also observe a negative correlation between functional capacity and the Fagerström questionnaire score (p=0.004;r=-0.3). We concluded that the smoke load and the nicotine dependence levels were related to worse quality of life indices of the smoking population.